2020
DOI: 10.1111/scs.12946
|View full text |Cite
|
Sign up to set email alerts
|

Use of simulation practices in public or community health nursing: findings from mixed‐methods systematic review

Abstract: Use of simulation practices in public or community health nursing: findings from mixed-methods systematic review Background: Simulation activities are valuable for nursing education and provide an experimental learning opportunity. However, simulation scenarios have focused on nursing education of traditional medical specialities, and limited research exists on simulation for community or public health nursing education. Aims: This study aimed to explore the methods that are being used to increase the knowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Simulated learning activities promote realistic problem-solving and critical thinking in a safe, controlled environment to prepare participants to function effectively in urgent situations (Society for Simulation in Healthcare, 2022). Using simulation in community settings improves critical thinking skills, group cooperation, an understanding of the different roles of participants, and overall confidence and competence (Aslan, 2021).…”
Section: Preparation Through Simulationmentioning
confidence: 99%
“…Simulated learning activities promote realistic problem-solving and critical thinking in a safe, controlled environment to prepare participants to function effectively in urgent situations (Society for Simulation in Healthcare, 2022). Using simulation in community settings improves critical thinking skills, group cooperation, an understanding of the different roles of participants, and overall confidence and competence (Aslan, 2021).…”
Section: Preparation Through Simulationmentioning
confidence: 99%
“…The simulation format may enhance critical thinking and confidence in taking actions. In systematic reviews and meta-analyses of simulation education literature, many investigators found that simulation education was beneficial in training medical (Capitani et al, 2021; Cook et al, 2013; Hovgaard et al, 2021) and nursing personnel (Aslan, 2021; Kim et al, 2016; Piot et al, 2022). However, we could not find contemporary research literature surrounding simulation-based patient-centered falls education.…”
Section: Introductionmentioning
confidence: 99%
“…TeamSTEPPS emphasizes training on communication and teamwork skills which can impact each of the aims for improving population health outcomes. Other teaching-learning strategies identified in the literature and on the Association of Community Health Nursing Educators (ACHNE)website include digital stories (LeBlanc, 2017), poster presentations(Rohlik & Krumwiede, 2020), case studies, and e-Learning modules(Eardley et al, 2018), video production(Kwon et al, 2021), role play, simulations(Aslan, 2020), videos, games, clickers, debates, photo journals, tabletop exercises, book discussions, and service-learning experiences (Association of Community Health Nursing Educators, 2022). [Correction added on 21 February 2023, after first online publication: In the preceding sentence, '(Association of Community Health Nursing Education, 2022)' has been corrected to '(Association of Community Health Nursing Educators, 2022)' in this version.]…”
mentioning
confidence: 99%